Mediated Influence of Entrepreneurship Education on MSME Business Performance: The Role of Orientation and Marketing (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: The objective of this study is to develop a mediated model that elucidates the relationship between entrepreneurship education and business performance. Methods: In this study, entrepreneurial orientation and entrepreneurial marketing were employed as mediators, while environmental competitiveness and bird-in-hand principles were used as moderators. The data were collected from 326 respondents who had completed four semesters of entrepreneurship education and who owned MSMEs, achieving a 98.7% response rate. The relationships were analysed through the implementation of structural equation modelling. Results: The impact of entrepreneurship education on business performance was not direct; however, it exerted a positive influence on entrepreneurial orientation, as evidenced by the findings of the study. Consequently, this dynamic shift has led to a notable enhancement in the realm of entrepreneurial marketing, thereby contributing to an observed improvement in business performance. The study's findings indicated that environmental competitiveness did not moderate the relationship between entrepreneurial marketing and business performance. Furthermore, the bird-in-hand principle did not demonstrate a moderating effect. Novelty: The novelty statement is particularly strong, positioning the